4lg(x)-6=2lg(x)

Simple and best practice solution for 4lg(x)-6=2lg(x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4lg(x)-6=2lg(x) equation:


Simplifying
4lg(x) + -6 = 2lg(x)

Multiply gl * x
4glx + -6 = 2lg(x)

Reorder the terms:
-6 + 4glx = 2lg(x)

Multiply gl * x
-6 + 4glx = 2glx

Solving
-6 + 4glx = 2glx

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Add '-2glx' to each side of the equation.
-6 + 4glx + -2glx = 2glx + -2glx

Combine like terms: 4glx + -2glx = 2glx
-6 + 2glx = 2glx + -2glx

Combine like terms: 2glx + -2glx = 0
-6 + 2glx = 0

Add '6' to each side of the equation.
-6 + 6 + 2glx = 0 + 6

Combine like terms: -6 + 6 = 0
0 + 2glx = 0 + 6
2glx = 0 + 6

Combine like terms: 0 + 6 = 6
2glx = 6

Divide each side by '2lx'.
g = 3l-1x-1

Simplifying
g = 3l-1x-1

See similar equations:

| gx=144 | | (x+1)(x-2)=(x-1)(x-1) | | -5/6=3/4n | | (3x-1)/(x-4)=0 | | 5x-8=3x-11+8 | | 2z-12-1=z-25+z | | 3/1728 | | 6(-2-3x)+8= | | -x-4=3x+6 | | -3-3x/21 | | 2(3m-9)-3(m-2)= | | 4x+5=8x+5 | | 7x-2=9x-4 | | 9x-9=19x-19 | | 11x-12=13x-20 | | 6x+3y=153 | | x+y=1.23 | | 5-x=32 | | 2x+15=13x+1 | | 10x+(12-x)=9x+12 | | 5x-1=10x-17 | | 19x+2=3x+14 | | 10/x=6.3681 | | 4.6/y=44.16 | | -32*Y=-22336 | | 10y+15x=5 | | (12-x)+x=12+36 | | (12-x)+x=12 | | 143=6x+17 | | 5(2y+4)=24 | | 8x+7=7x-3 | | W-(-322)=-728 |

Equations solver categories